The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1413-70542011000600015
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of Diabrotica speciosa germar (coleoptera: chrysomelidae)

Abstract: Entomopathogenic nematodes (EPNs) are used in biological control of soil insects and show promise in the control of D. speciosa. The objective of this work was to evaluate the potential of native and exotic entomopathogenic nematode isolates in the control of D. speciosa under laboratory and greenhouse conditions. Results showed that all of EPNs caused larval mortality. The most virulent were Heterorhabditis sp. RSC01 (94%), Steinernema glaseri (84%), Heterorhabditis sp. JPM04 (82%) and Heterorhabditis amazone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Diabrotica speciosa, also called green cow or patriot, has been detected in most crops in South America. In Brazil, the adult pest is considered an important pest infesting some extensive crops, such as soybeans [26], [27]. The pest that prefers the softer leaves and damages plants by eating small round holes in the leaf or making incisions on the leaf edges [12].…”
Section: A Soybean Plants Damages By Caterpillars and Diabrotica Spec...mentioning
confidence: 99%
“…Diabrotica speciosa, also called green cow or patriot, has been detected in most crops in South America. In Brazil, the adult pest is considered an important pest infesting some extensive crops, such as soybeans [26], [27]. The pest that prefers the softer leaves and damages plants by eating small round holes in the leaf or making incisions on the leaf edges [12].…”
Section: A Soybean Plants Damages By Caterpillars and Diabrotica Spec...mentioning
confidence: 99%
“…Similar results have been obtained for South American species. In Brazil, the microbial control of D. speciosa larvae with entomopathogenic fungi or nematodes is considered to have great potential because the soil is a relatively stable environment in terms of temperature and humidity, especially in no-till farming [ 111 ]. Argentine strains of M. anisopliae and B. bassiana killed third instars of D. speciosa in the laboratory [ 112 ].…”
Section: Control Of South American Diabroticamentioning
confidence: 99%
“…Laboratory and greenhouse Santos et al [25] Sugar cane borer Fowler [47] evaluated soil samples of 1,532 locations, adding mole crickets of the genera Scapteriscus and Neocurtilla (Orthoptera: Gryllotalpidae) as insect bait, and obtained 18 isolates of S. feltiae and 13 isolates of Heterorhabditis spp. Some authors suggested that those Steinernema isolates may have been misidentified, and in fact they could be Steinernema scapterisci, later described by Nguyen & Smart [48] in 1990.…”
Section: H Amazonensis and Steinernema Glaserimentioning
confidence: 99%
“…In Brazil, this type of application has proved to be effective to control pests on different crops. In greenhouse experiments, the application of aqueous suspensions has been found to be effective against Conotrachelus psidii Marshall (Coleoptera: Curculionidae) (guava weevil) [13] , Mahanarva spectabilis (Distant) (Hemiptera: Cercopidae) (spittlebug) [86] , Diabrotica speciosa (Germar) (leaf beetle) [25] , Sphenophorus levis Vaurie (Coleoptera: Curculionidae) (sugarcane weevil) [16] and Dysmicoccus texensis (Tinsley) (Hemiptera, Pseudococcidae) [19] . With respect to field trials, good results have been obtained against M. fimbriolata (sugarcane root spittlebug) [11] , C. psidii [13] , Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) (fruit fly), Anastrepha fraterculus (Wied.)…”
Section: Applicationmentioning
confidence: 99%